Is social media hindering or helping academic performance? A case study of Walter Sisulu University, Buffalo City Campus - Agbeyangi, A.; Lukose, J. (South African Journal of Higher Education, 2024)
Social media platforms are popular among higher education students and have seen increased usage for academic purposes, especially during the COVID-19 pandemic. However, excessive use of social media can negatively impact students’ academic performance. This preliminary study examines social media’s impact on students’ academic performance at Walter Sisulu University (WSU), Buffalo City campus. Using a positivist paradigm and a quantitative approach, randomly sampled data were collected from 71 students through a survey to identify trends and generate preliminary insights. Results indicate that while social media can facilitate academic work, it predominantly acts as a distraction, negatively affecting academic performance, particularly for first-year students. Notably, 84.5 per cent of the students spend more than four hours daily on social media, and 39.4 per cent agree that it negatively impacts their assignment completion. The study underscores the need for students to balance their social media use and academic responsibilities, highlighting the importance of this issue. Recommendations for achieving this balance, such as adopting time management strategies and integrating social media into teaching methodologies, are discussed.